Multirod Pumping Approach with Fresnel Lens and Ce:Nd:YAG Media for Enhancing the Solar Laser Efficiency - Joana Almeida; Hugo Costa; Cláudia R. Vistas; Bruno D. Tibúrcio; Ana Matos; Dawei Liang (Energies)
A multirod Ce:Nd:YAG solar laser approach, using a Fresnel lens as a primary concentrator, is here proposed with the aim of considerably increasing the efficiency of solar-pumped lasers. Fresnel lenses are cost-effective, rendering solar lasers more economically competitive. In this work, solar-pumped radiation collected and concentrated using the Fresnel lens is received by a secondary three-dimensional compound parabolic concentrator which transmits and funnels the light toward the Ce:Nd:YAG laser rods within a water-cooled tertiary conical concentrator that enables efficient multipass pumping of the rods. To explore the full potential of the proposed approach, the performance of various multirod configurations is numerically evaluated. Through this study, configurations with three and seven Ce:Nd:YAG rods are identified as being the most efficient. A maximum continuous wave total laser power of 122.8 W is reached with the three-rod configuration, marking the highest value from a Ce:Nd:YAG solar laser, leading to solar-to-laser conversion and collection efficiencies of 7.31% and 69.50 W/m2, respectively. These results represent enhancements of 1.88 times and 1.79 times, respectively, over the previous experimental records from a Ce:Nd:YAG/YAG single-rod solar laser with a Fresnel lens. Furthermore, the above results are also 1.58 times and 1.68 times, respectively, greater than those associated with the most effective three-rod Ce:Nd:YAG solar laser utilizing a parabolic mirror as the main concentrator. The present study also shows the great usefulness of the simultaneous pumping of multiple laser rods in terms of reducing the thermal stress effects in active media, being the seven-rod configuration the one that offered the best compromise between maximum efficiency and thermal performance. This is crucial for the applicability of this sustainable technology, especially if we wish to scale our system to higher power laser levels.